The Second International Scientific and Practical Conference «Current Trends in Breeding and Seed Production of Vegetable Crops: Traditions and Perspectives» - V.F. Pivovarov; O.N. Pishnaya; L.K. Gurkina (Овощи России)
On 2-4 August at All-Russian Research Institute of Vegetable Breeding and Seed Production the Second International Scientific and Practical Conference «CURRENT TRENDS IN BREEDING AND SEED PRODUCTION OF VEGETABLE CROPS: TRADITIONS AND PROSPECTS» was held to be dedicated to 90 years since VNIISSOK was established.